Relations between Ecuador and Colombia: an example of the need for a democratic foreign policy - Ponce Leiva, Javier (2016)
The author reviews Ecuador's foreign policy towards Colombia, which is considered as a deficient one. This article analyzes such issues as the absence of an elementary domestic consensus, the precarious coordination between civil and military officials, the weak links between domestic policies and foreign policy, and the lack of a specific agenda towards Colombia. The author recommends developing a foreign policy based on a well-established agenda, which should give priority to domestic goals.